Protected Areas, National Parks and Sustainable Future - Naqiyuddin Bakar, Ahmad; Nazip Suratman, Mohd (IntechOpen, 2020)
This book aims to examine the context and practice of national parks regarding a countries' obligations to safeguard biodiversity through the protection and management of forest-protected areas. The book examines the wider impacts of national parks within the scope of an integrated environmental hub at the global and regional level and eventually delves into the country case. Three areas are covered: theoretical underpinnings and concepts related to national parks, exploring their various modalities and integrated concerns for the environment; an empirical review in lieu of effective management of protected areas as defined by the World Conservation Union IUCN, addressing the efficient use of human and material resources, including national/agency-protected area regulations and legislation, policies, international conventions and designations, management plans, and/or agreements associated with those areas; and evaluation of challenges underlying a country's intention to gauge the potential of a national park and pinpoint adequate attention on exploiting new strategies for national park management.